Current indications for pegging in the anophthalmic socket: are there any?. Issue 5 (September 2016) - Jordan, David R.; Stoica, Bazil; Klapper, Stephen R.
Abstract : Purpose of review: To highlight the development, problems, and current status of coupling porous orbital implants to the overlying prosthetic eye. Recent findings: Although increasing the risk of complications, pegging significantly contributes to prosthesis motility and satisfies the cosmetic expectations of some patients. Patients should be counseled regarding the increased risks in approximately one-third of individuals and that complications can occur even 10 years following implantation. Summary: Although implant peg placement has declined dramatically over the past decade, a precise and meticulous technique under intravenous anesthesia in the appropriately selected patient can be a successful outpatient procedure. Fortunately, most problems are of a minor nature, and over 85% of patients are able to retain their pegs following proper management and timely intervention. Additional visits to the ophthalmic plastic surgeon or ocularist are required that may not be necessary if a peg had not been placed.